1995
DOI: 10.1002/hep.1840210604
|View full text |Cite
|
Sign up to set email alerts
|

Low prevalence of hepatitis C virus infection in porphyria cutanea tarda in germany

Abstract: Previous studies from Spain, Italy, and France have demonstrated a high prevalence (71% to 91%) of antibodies against hepatitis C virus in patients with porphyria cutanea tarda (PCT). To determine the role of hepatitis C virus (HCV) in PCT in Germany, we have assessed the prevalence of antibodies against HCV and hepatitis B virus (HBV) in 106 patients (mean age, 60 +/- 14 years) with the disease. Eight of 106 patients (8%) were positive for HCV antibodies and HCV RNA using second-generation enzyme-linked immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
1
13

Year Published

1996
1996
2008
2008

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(45 citation statements)
references
References 24 publications
0
31
1
13
Order By: Relevance
“…However, recent studies in Spain, France, and Italy [4][5][6] indicated that a substantial majority (71%-91%; average, 77%) of subjects with PCT had evidence of infection with the hepatitis C virus (HCV). In contrast, the prevalence of HCV infection was low (0%-18%) in PCT patients from Northern or Central Europe, 3,[7][8][9][10] Australia, 11 or New Zealand. 12 Until now, the relationship of HCV to PCT has been studied in few North American patients.…”
Section: And Elder 3 )mentioning
confidence: 99%
“…However, recent studies in Spain, France, and Italy [4][5][6] indicated that a substantial majority (71%-91%; average, 77%) of subjects with PCT had evidence of infection with the hepatitis C virus (HCV). In contrast, the prevalence of HCV infection was low (0%-18%) in PCT patients from Northern or Central Europe, 3,[7][8][9][10] Australia, 11 or New Zealand. 12 Until now, the relationship of HCV to PCT has been studied in few North American patients.…”
Section: And Elder 3 )mentioning
confidence: 99%
“…The identification of chronic viral hepatitis C as a frequent coexisting disease in porphyria cutanea tarda (PCT) with an increasing gradient from northern to southern Europe (1)(2)(3)(4) suggests association between viral hepatitis and porphyrinopathies. Increased urinary porphyrin excretion has been recognised for many years in various hepatobiliary diseases (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…In Italy and in other Mediterranean countries hepatitis C virus (HCV) infection is the single most frequent cause of liver disease in PCT patients, 6,21,22 while it is rare in Northern European countries. 23,24 The aim of this work is to investigate whether HFE mutations have a role as genetic susceptibility factors for PCT in a population with a high prevalence of an acquired triggering factor, such as HCV chronic infection.…”
mentioning
confidence: 99%